В почследнем ошибка В последнем
26х = -4/2
26х= -2
х= -2/26
х= -1\13
Преобразуем выражения, воспользовавшись следующими свойствами степеней:
а^c * b^c = (ab)^c,
(a^b)^c = a^(bc),
a^b * a^c = a^(b + c).
x * x^3 * x * x^7 = x^(1 + 3 + 1 + 7) = x^12.
(-2a)^2 * (-2a) * (-2a)^5 = (-2a)^(2 + 1 + 5) = (-2a)^8 = (-1)^8 * 2^8 = 1 * 2^8 = 2^8.
c^m * c * c^2 * c^(m+1) * c = c^(m + 1 + 2 + m + 1 + 1) = c^(2m + 5).
5 * 125 * 25 = 5 * 5^3 * 5^2 = 5^(1 + 3 + 2) = 5^6.
8 * 32 * 16 = 2^3 * 2^5 * 2^4 = 2^(3 + 5 + 4) = 2^12.
3^n * 27 * 3^(n – 4) * 9 = 3^n * 3^3 * 3^(n – 4) * 3^2 = 3^(n + 3 + n – 4 + 2) = 3^(2n + 1).
(12/41)^(x/26)+1=(51/44)^(x/26)+1,
(12/41)^(x/26)=(51/44)^(x/26),
(12/41 * 44/51)(x/26)=1,
(176/697)^(x/26)=1,
x/26=0,
x=0,
(7/8)^((x-1)/2)= ²⁶√8/7,
(7/8)^((x-1)/2)= (7/8)^(-1/26),
(x-1)/2=-1/26,
x-1=-1/13,
x=12/13,
8=1/(4^(26x+1)),
(2^(-2))^(26x+1))=2^3,
-2(26x+1)=3,
26x+1=-3/2,
26x=-5/2,
x=-5/52.